Integrating Design Thinking into Blended Learning to Develop Critical Thinking in Thai General Practitioners - Daengneam, Bancha; Sovajassatakul, Thanongsak; Sriwisathiyakun, Kanyarat (Journal of Cultural Analysis and Social Change, 2025)
This study developed and piloted a blended learning model integrating design thinking to enhance critical thinking skills among Thai general practitioners (GPs), for whom such skills are essential yet challenging to cultivate. Using a two-phase research and development approach, the model was first drafted and validated by an expert panel (n = 5), receiving high ratings for quality and appropriateness (M = 4.57, SD = 0.21). Subsequently, a single-arm pilot study with 30 Thai GPs demonstrated significant post-intervention improvements in both knowledge (from M=55.56 to M=71.36, p<.001) and critical thinking skills (from M=3.36 to M=4.86, p<.001). The findings confirm the model's feasibility and initial effectiveness, providing a strong rationale for a future randomized controlled trial.